Next Generation of Leadership-as-Practice: Reconceptualizing Change - Joseph A. Raelin; Marian Iszatt-White; Brigid Carroll; Lucia Crevani; Brandon Kliewer; Jennifer L. Robinson (Journal of Change Management, 2025)
This special issue features some new studies that are referred to by the editorial team as “second generation” research in the field of leadership-as-practice (L-A-P). Consistent with this journal's title, Journal of Change Management: Reframing Leadership and Organizational Practice, this issue focuses on those sociomaterial practical accomplishments and turning points that change trajectories within the flow of practice thus producing leadership. In this second generation of L-A-P studies, writers would begin to establish the boundary conditions that explicitly define the field's interpretation of leadership, especially its concentration on collective change agency. This essay as well as the accompanying four papers through the exploration of un- and under-explored areas thus intend to contribute to further L-A-P theoretical development and application. In particular, the special issue begins to resolve where and when leadership within the flow of practice actually occurs, how it integrates with but also differentiates from other plural leadership traditions, which kinds of applied practices can enhance applications in organizational learning and development, and lastly how agency can be mobilized through the interconnection between current and dispersed chains of activity over time and across space.
Keywords: J24; M10; M14; M12; M53; M54; 330; Leadership-as-Practice; Leadership; Collective change agency; Flow of practice; Organizational change; Practice theory